Enhancing The Role of Parliament in Budget Transparency, Public Participation and Budget Oversight: Review of Open Budget Survey Results In 2023 - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
The results of the Open Budget Survey (OBS) in 2023 coducted by the International Budget Partnership (IBP) showed that, the score for the transparency dimension did not change from the 2021 survey, which amounted to 70. The score for the public participation dimension increased from 24 in 2021, to 26 in 2023. The score for the budget oversight dimension decreased from 61 in 2021 to 59 in 2023 due to lack of evidence of session report of the commitees both in areas of budget oversight and audit report from State Audit Institution (SAI). This article aims to discuss the results of OBS related to the Indonesian parliament and relate them to the mechanism of parliamentary work and the laws and regulations governing the implementation of parliamentary duties. The research method used is descriptive qualitative with the results of the 2023 OBS questionnaire as the main document used in this research. The results show that the parliament needs to improve its mechanisms for periodic monitoring of SAI audit reports, monitoring the implementation of the current fiscal year of 2025 and improving public participation mechanism in budget discussions within and outside the APBN cycle.